Improving Student Learning Outcomes Using the Demonstration Method with "Rule Conversion" Media on Length Conversion Material in Primary School - Ita Sri Rahayu; Elmi Listyoningsih; Yeni Rakhmawati (Journal of Learning Improvement and Lesson Study, 2022)
Mathematics is the study of interconnected values and concepts. This study is motivated by the problems of students in learning mathematics unit length conversion material class IV MI Islamiyah, learning unit length conversion material unsatisfactory learning outcomes due to lack of learning media that can attract students' attention. The purpose of this study is to improve student learning outcomes using the demonstration method through rule conversion media in the material of converting units of length in class IV MI Islamiyah. This research is a Classroom Action Research consisting of 2 cycles. The research subjects were grade IV MI Islamiyah students totaling 15 students. This research data use formative tests and observation sheets. The analysis technique used is the quantitative descriptive analysis technique. The results showed an increase in observation of teacher activeness from cycle I to cycle II by 65% and 92% (an increase of 27%) and observation of student activeness by 46% and 89% (an increase of 27%). 43%), and the average student score was 71 (46%) to 81 (80%). Based on these results, it can be seen that the use of rule conversion media can improve the test scores of grade IV MI Islamiyah students on the material of length unit conversion.